PENGARUH MEDIA PEMBELAJARAN MATEMATIKA BERBASIS WINGEOM TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA MTSN DANAU KERINCI - Heswari, Sonya; Patri, Sonya Fiskha Dwi (Universitas Muhammadiyah Bengkulu, 2020)
This study aims to look at the effect and interactions that occur between teaching materials by wingeom and early mathematics abilities on student’ mathematical understanding skills. This type of research is quasi-experimental researh. The population in this study were students class VIII of MTsN Danau Kerinci which numberrer 5 classes. The sample was selected using simple random sampling techniques, there was class VIIIA as the experimental class and class VIIIB as the control class. The research design used was the posttest only control group design. During the research, the experimental class was treated with learning by wingeom teaching material, while the control class was treated with conventional learning. The technique of collecting data through a test of mathematical understanding skills was anilyzed using two-way ANOVA. The result are (1) there is a difference between students’ mathematical understanding ability base on the teaching materials, Fcount=4,982 Fα=4,12 (2) there isa difference between students’ mathematical understanding ability viewed from early mathematics ability (high, medium, an low categories), Fhitung=29,315 Fα=3,27 (3) an interaction between the teaching materials and the student categories with early mathematics ability, Fhitung=-0,4 Fα=3,27Keywords : Mathematical Understanding Ability, Teaching materials by wingeom, Early Mathematics Ability